Increasing Body Temperature of Hypothermic Patients Post Anesthesia Subarachnoid Block with Fluid Warmer and Blanket Warmer - Mahin, Ahmad; Mawaddah, Nurul; Sudiyanto, Henry (PT Saintek Medika Nusantara, 2022)
Hypothermia causes discomfort to the patient and leads to dangerous complications. Nonpharmacological treatments for hypothermia include using fluid warmers and blanket warmers. This study aimed to determine the difference in the effectiveness of fluid warmers and blanket warmers on the body temperature of hypothermic patients after subarachnoid block anesthesia. This research is a quasi-experiment with a non-equivalent comparison group design. The research subjects included hypothermic patients after subarachnoid block anesthesia in the Recovery Room of Dr. Mohamad Soewandhie Surabaya Hospital. The sample amounted to 82 people divided into 2 groups: 41 in the fluid-warmer group and 41 in the blanket-warmer group. The sampling technique used was Simple Random Sampling. Data analysis using Paired T-Test and Independent T-Test. The results showed that after 30 minutes, the average increase in body temperature in the fluid warmer group was 1.78oC, the average increase in body temperature in the blanket warmer group was 1.18oC, and the difference in the average value of body temperature increase between the fluid warmer and blanket warmer groups was 0.59oC. The p-value in the Independent T-Test test results is 0.000. Based on decision-making in the Independent T-Test Test, the p-value is less than 0.05, meaning that the average body temperature increase between the fluid-warmer and blanket-warmer groups is significantly different. Looking at the results of the above study, it can be concluded that there are differences in the effectiveness of fluid and blanket warmers on the body temperature of patients with hypothermia after subarachnoid block anesthesia. Among the two interventions, the use of fluid warmers is a therapy that is more effective in increasing the body temperature of hypothermic patients after subarachnoid block anesthesia, so researchers suggest that the use of fluid warmers can be used as an option therapy in increasing the body temperature of hypothermic patients.